Beyond 'State Ibuism': Empowerment Effects in State‐led Development in Indonesia. Issue 5 (20th December 2017) - Jakimow, Tanya
ABSTRACT: This article examines the ways women's processes of self‐formation are indicative (or not) of new possibilities for women's gendered selves in the post‐Reformasi period in Indonesia. It focuses on the development arena to reveal how shifts in state rhetoric, from top‐down guidance based on a patriarchal familial model to bottom‐up, inclusive development based on empowerment, have transformed what is referred to as the 'topography for self'. The article draws upon theories of personhood a) to show how gendered selves emerge and are contested within particular historical conditions; and b) to develop an alternative framework of 'empowerment' that focuses not on capabilities and choice, but on an expansion in the possibilities for self. It argues that models of community‐driven development have provided new opportunities for women to hold and enact socially recognizable subject positions. This constitutes a form of empowerment for individual women but does not necessarily reflect challenges to patriarchy in Indonesia.